Low birth weight and chronic energy deficiency in the mother lead to stunting: a case-control study - Nida Faradisa Fauziyah; Aliffia Setyawibowo Putri (International Journal of Health Science and Technology, 2023)
Stunting, a malnutrition problem, is defined as shorter in height than its peers. Indonesia has Southeast Asia's third-highest stunting rate, averaging 36.4% from 2005 to 2017. Stunting requires special attention because it interferes with the optimal development of children, causes mortality, and pain, and inhibits the development of movement skills. The study aimed to analyze the relationship between Low Birth Weight (LBW) and a history of Chronic Energy Deficiency (CED) in mothers with stunting. The study used an observational analytic case-control study design using secondary data, with a case-control ratio of 1:1. Toddlers aged 0 to 5 are included. They are using purposive sampling with 142 samples. The results of the study were samples of toddlers aged 0-5 years, male sex as much as 86 (60.6%), low birth weight as much as 80 (56.3%), chronic energy deficiency in mothers as much as 88 (62%). The chi-square test results show a relationship between low birth weight and the incidence of stunting with p 0.000 0.05 and a relationship between a history of chronic energy deficiency in mothers to stunting with p 0.000 0.05. According to the logistic regression test findings, LBW has an OR of 26.83 with stunting, and a history of chronic energy deficiency in mothers has an OR of 4.4 with stunting. The study concluded a close relationship between low birth weight (LBW) and a history of chronic energy deficiency (CED) and stunting incidence.